EVALUATION OF FETAL WEIGHT SONOGRAPHICALLY USING AREA OF WHARTON'S JELLY AND MORPHOLOGY OF UMBILICAL CORD - Senapati, Susmita; Behera, Shashi Shankar; Chinara, Prafulla Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To establish a sonographic relationship between Area of Wharton's Jelly (AWJ) and umbilical cord morphometry with the birth weight of the fetus in low-risk pregnancies from 13 to 40 weeks. Methods: A total of 800 singleton pregnant females were subjected for routine sonographic evaluation. The umbilical cord length, diameter, and AWJ were determined. The gestational age and fetal weight were determined using usual fetal parameters. Umbilical cord morphometry along with Area of Wharton Jelly can be utilized as other parameters to increase the accuracy of fetal weight. Results: In our study, the umbilical cord diameter at birth showed statistically significant positive correlation with birth weight (R=0.167; p<0.001). Umbilical cord length, diameter, and Area of Wharton Jelly showed statistically significant positive correlation with birth weight (p<0.001). Conclusion: Using statistical analysis, a positive correlation was established between estimated fetal weight and fetal age with umbilical cord morphometry and AWJ.